Rapid and Specific Action of Methylene Blue against Plasmodium Transmission Stages - Nathanaël Saison; Jean-François Franetich; Yudi T. Pinilla; Anton Hoffmann; Stravensky T. Boussougou-Sambe; Barclaye Ngossanga; Maurel Tefit; Kutub Ashraf; Nadia Amanzougaghene; Shahin Tajeri; Ayola A. Adegnika; Dominique Mazier; et al. (MDPI AG, 2022)
Methylene blue (MB) is the oldest synthetic anti-infective. Its high potency against asexual and sexual stages of malaria parasites is well documented. This study aimed to investigate possible additional activities of MB in interfering with parasite transmission and determine target stages in Anopheles vectors and humans. MB's transmission-blocking activity was first evaluated by an ex vivo direct membrane feeding assay (DMFA) using Plasmodium falciparum field isolates. To investigate anti-mosquito stage activity, Plasmodium berghei-infected Anopheles stephensi mosquitoes were fed a second blood meal on mice that had been treated with methylene blue, 3, 6- and 15-days after the initial infectious blood meal. Anti-sporozoite and liver stage activities were evaluated in vitro and in vivo via sporozoite invasion and liver stage development assays, respectively. MB exhibited a robust inhibition of P. falciparum transmission in An. gambiae, even when added shortly before the DMFA but only a moderate effect against P. berghei oocyst development. Exposure of mature P. berghei and P. falciparum sporozoites to MB blocked hepatocyte invasion, yet P. berghei liver stage development was unaffected by MB. Our results indicate previously underappreciated rapid specific activities of methylene blue against Plasmodium transmission stages, preventing the establishment of both mosquito midgut and liver infections as the first essential steps in both hosts.